The association between higher FFAs and high residual platelet reactivity among CAD patients receiving clopidogrel therapy - Zhao, Zehao; Dong, Shutong; Sun, Tienan; Han, Kangning; Huang, Xin; Ma, Meishi; Yang, Shiwei; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2023)
Background Metabolic abnormalities are associated with the occurrence, severity, and poor prognosis of coronary artery disease (CAD), some of which affect the antiplatelet efficacy of clopidogrel. Free fatty acids (FFAs) is a biomarker for metabolic abnormalities, and elevated FFAs is observed among CAD patients. Whether FFAs enhances residual platelet reactivity induced by adenosine diphosphate (ADP) while using clopidogrel was unknown. The purpose of our study is exploring the issue. Method Current study included 1,277 CAD patients using clopidogrel and used logistic regression to detect whether the higher level of FFAs is associated with high residual platelet reactivity (HRPR). We additionally performed subgroup and sensitivity analyses to evaluate the stability of the results. We defined HRPR as ADP-induced platelet inhibition rate (ADPi) < 50% plus ADP-induced maximum amplitude (MAADP) > 47 mm. Results 486 patients (38.1%) showed HRPR. The proportion of HRPR among patients with higher FFAs (>0.445 mmol/L) is greater than among patients with lower FFAs (46.4% vs. 32.6%, P < 0.001). Multivariate logistic regression demonstrated that higher FFAs (>0.445 mmol/L) is independently associated with HRPR (adjusted OR = 1.745, 95% CI, 1.352–2.254). After subgroup and sensitivity analyses, the results remained robust. Conclusion The higher level of FFAs enhances residual platelet reactivity induced by ADP and is independently associated with clopidogrel HRPR.